Bioethanol Production of Cellulase Producing Bacteria from Soils of Agrowaste Field - Thomas, A.; Laxmi, M.; Benny, A. (Journal of Scientific Research, 2021)
With decades of studies on cellulose bioconversion, cellulases have been playing an important role in producing fermentable sugars from lignocellulosic biomass. Copious microorganisms that are able to degrade cellulose have been isolated and identified. The present study has been undertaken to isolate and screen the cellulase producing bacteria from soils of agrowaste field. Cellulase production has been qualitatively analyzed in carboxy methylcellulose (CMC) agar medium after congo red staining and NaCl treatment by interpretation with zones around the potent colonies. Out of the seven isolates, only two showed cellulase production. The morphogical and molecular characterization revealed its identity as Escherichia coli and Staphylococcus aureus. The potential of organisms for bioethanol production has been investigated using two substrates, namely, paper and leaves by subjecting with a pre-treatment process using acid hydrolysis to remove lignin which acts as physical barrier to cellulolytic enzymes. Ethanolic fermentation was done using Saccharomyces cerevisiae for 24-48 h and then the bioethanol produced was qualitatively proved by iodoform assay. These finding proves that ethanol can be made from the agricultural waste and the process is recommended as a means of generating wealth from waste.